KEPENTINGAN INDONESIA MELAKUKAN IMPOR GANDUM DARI AUSTRALIA TAHUN 2012-2016 - Fitri Nurhalimah; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This thesis is a Bilateral Trade study that analysis Indonesia's interests in meeting domestic food needs. This research focused on Indonesia's interests in importing wheat from Australia  in  2012-2016. Wheat is the most food commodity produced in the world compared to maize and rice, even the number of production from year to year is increasing. As a country with high consumption of wheat Indonesia imports from world wheat producers such as Australia.This thesis usesd the theory of International Trade where there is a bilateral relationship between two countries by carrying out export-import. Supported by the level of analysis of the Nation State and the Liberalism Perspective. The concept refers to the method of qualitative methods and assisted by Library Research as a source of information.          Indonesia's interest in importing wheat is due to increased consumption of wheat in the country. Australian wheat contributes 97-99 percent of Australian grain exports to Indonesia every year. Australia exported an average of 4.0 million tons of wheat over the past five years and another factor that affected it was the proximity of the region between the two countries. Keywords:IA-CEPA, interest, import, wheat.